OVERVIEW OF MUCOADHESIVE BIOPOLYMERS FOR BUCCAL DRUG DELIVERY SYSTEMS - PURI, VIVEK; SHARMA, AMEYA; MAMAN, PARAMJOT; RATHORE, NISHANT; SINGH, INDERBIR (International Journal of Applied Pharmaceutics, 2019)
Mucoadhesive dosage forms may be intended for facilitation of prolonged retention time at the application site hence providing drug release in a controlled rate for enhanced improvement of therapeutic activity and its outcome. The buccal mucosa has been investigated for systemic drug delivery and local drug treatment or therapy that is subjected to first pass metabolism. The applicability of bio-adhesion approach in buccal drug delivery proved great therapeutic potential to overcome the limitation of conventional buccal drug delivery. The delivery via buccal route using mucoadhesive biopolymers such as various natural gums e.g. carrageenans, gum karaya, gum arabic, locust bean gum, khaya gum, gum ghatti, albizia gum, guar gum, starch, cellulose, larch gum and pectin etc. and various thiolated and carboxymethylated polymers has been the subject of interest since the early 20th century. The present article is focused mainly on the oral mucosa, mechanism of drug permeation, and characteristics of the desired polymers, the manuscript then proceeds to cover the theories behind the adhesion of bioadhesive polymers to the mucosal epithelium followed by the factors affecting mucoadhesion. Further the author has also discussed on the new generation of mucoadhesive polymers and their properties, recent mucoadhesive formulations for enhanced buccal drug delivery, various marketed products and patent literature. Various online search engines and scientific journals were employed for the collection of literature and scientific data and information related to the topic using keywords like mucoadhesive polymers, buccal drug delivery, buccal patches, tablets, films, gels, powder from the year 2002 and above.